Culture and society, 1780-1950 - Williams, Raymond (Penguin Books, 1963)
In the last decades of the eighteenth century, and in the first haft of te nineteeth century, a number of words, which are now of capital importance, came for the first time into common English use, or, where they had already been generally used in the language, acquired new and important meanings...